2017
DOI: 10.1002/jssc.201601190
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of magnetic molecularly imprinted polymer nanoparticles by surface imprinting by a sol-gel process for the selective and rapid removal of di-(2-ethylhexyl) phthalate from aqueous solution

Abstract: Magnetic molecularly imprinted polymer nanoparticles for di-(2-ethylhexyl) phthalate were synthesized by surface imprinting technology with a sol-gel process and used for the selective and rapid adsorption and removal of di-(2-ethylhexyl) phthalate from aqueous solution. The prepared magnetic molecularly imprinted polymer nanoparticles were characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis, and vibrating sample magnetometry. The adsorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…To measure the efficiency and stability of the imprinted polymers, five regeneration cycles were performed with a standard solution of imidacloprid. The results (Supporting Information Figure S2) showed that the polymer efficiency slightly decreased (by 6%) over the five consecutive regeneration cycles, which might be due to loss of the imprinted sites during regeneration . This proved that the synthesized polymers were stable and could be efficiently reused.…”
Section: Resultsmentioning
confidence: 92%
“…To measure the efficiency and stability of the imprinted polymers, five regeneration cycles were performed with a standard solution of imidacloprid. The results (Supporting Information Figure S2) showed that the polymer efficiency slightly decreased (by 6%) over the five consecutive regeneration cycles, which might be due to loss of the imprinted sites during regeneration . This proved that the synthesized polymers were stable and could be efficiently reused.…”
Section: Resultsmentioning
confidence: 92%
“…To determine the adsorption mechanism, three classical isothermal adsorption models, Langmuir, Freundlich, and Tempkin equations, were used to analyze the adsorption data of the MMIP and MNIP for atrazine. These adsorption models can be described by the following equations [5]:…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Moreover, the currently used technologies are non-selective. Due to its high efficiency and easy operation, adsorption is one of the most important methods for removal of organic pollutants [5,6]. Adsorbents used in pesticide remediation from water and wastewater have been already developed [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…When MNPs are used as adsorbents, the developed SPE is designated as magnetic solid‐phase extraction (MSPE) to distinguish from the traditional SPE. In the past decade, a large number of functionalized MNPs have been synthesized and used in MSPE for various pollutants, including metal ions , phenolic compounds , pesticides , and phthalates .…”
Section: Introductionmentioning
confidence: 99%